2015
DOI: 10.1097/bot.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Augmented Plate Fixation for the Treatment of Vertical Shear Femoral Neck Fractures

Abstract: The strength of surgical repairs of the vertical shear femoral neck fractures can be significantly augmented with the 2.7-mm locking plate. The construct with the cannulated screws was significantly stronger than the DHS construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 16 publications
1
62
1
Order By: Relevance
“…[1923] Pauwels grade-3 femoral neck fracture treatment should be based on the individual characteristics of patient and fracture feature. Factors including fracture displacement, comminution, invasion of operation, meanwhile, surgeon's experience should also be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…[1923] Pauwels grade-3 femoral neck fracture treatment should be based on the individual characteristics of patient and fracture feature. Factors including fracture displacement, comminution, invasion of operation, meanwhile, surgeon's experience should also be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Buttress plates placed against the medial cortical bone have been previously reported. Sarat C. Kunapuli et al [29] introduced an augmenting fixation with a 2.7-mm limited contact dynamic compression (LCDC) plate, contoured to fit along the anterior. Subsequently, Hak et al [17] reported a novel procedure that combines cannulated screws with a medialbuttress 1/3 tubular plate, which is contoured during surgery based on the patients' anatomical structure.…”
Section: Discussionmentioning
confidence: 99%
“…72 The plate augmentation increased the energy absorbed to failure by an average of 187%. Buttress plates are applied over the apex of fractures and act by resisting shear forces and converting them into compressive forces.…”
Section: Augmentation Technique: Buttress Plating Of the Femoral Neckmentioning
confidence: 99%